Agronomic properties and nutritive value of Aleman grass (Echinochloa polystachya) established under different soil type and drainage condition - Ahmad Zabidi, Nurfateha (2015)
The agronomic properties and nutritive value of Aleman grass (Echinochloa polystachya) under different types of soil and drainage condition were assessed in six month experiment from early April 2014 until September 2014 at Field 15, Universiti Putra Malaysia (UPM) using factorial experiment of completely randomised design (CRD). The treatments used was the drainage condition (dry and waterlogged) and types of soil (Munchong series, Malacca series, Serdang series, and ex-mining Alluvium soil) that were cultivated in pot sized 19 cm x 26 cm and arranged on 6 m x 5.4 m land area. The agronomic properties and the nutritive value were assessed and the grass was sample and was cut at 15 cm height above the ground level every 21 days. The chemical composition was analyzed for dry matter (% DM), ash (% OM), crude protein (% CP), neutral detergent fibre (% NDF), acid detergent fibre (% ADF), and acid detergent lignin (%ADL) at the Nutrition Laboratory, Department of Animal Science, Faculty of Agriculture, UPM. The agronomic properties assessed are plant height, tiller number per plant, dry matter production, and leaf to stem ratio and root to shoot ratio. Plant height was significantly different (P>0.05) in both treatments, but, other parameters show no significant difference between treatments. In terms of nutritive value, there were significance differences (P<0.05) on crude protein (% CP) and neutral detergent fibre (% NDF) under dry and waterlogged condition. Meanwhile, there was no significant effect on dry matter (% DM), ash (% OM), acid detergent fibre (% ADF), and acid detergent lignin (% ADL) content between treatments. There were also non significant differences on DM, OM, ADF and ADL under dry condition, but show a significant difference in waterlogged condition. The grass grown under waterlogged condition exhibit higher growth, well develop and better production in four different types of soil. There is only significantly difference of plant height on both condition, but other parameters show a significant difference under different types of soil. However, there were some effects at dry condition under different types of soils in the study. The result shows a lower production and performance at dry condition. All parameters show non significant difference in dry condition except for plant height, %CP and %NDF content. It is concluded that the grass grown under waterlogged condition gave the best result for agronomic properties and nutritional content under difference types of soil. Besides that, the Aleman grass show a positively impact to grown under ex-mining Alluvium soil as compared to other types of soil. Then, it is strongly recommended that the Aleman grass should be planted in waterlogged condition and under ex-mining Alluvium soil to produce higher production that is useful to replace Napier and Guinea grass in the future.